2019
DOI: 10.1093/jcr/ucz039
|View full text |Cite
|
Sign up to set email alerts
|

Good Vibrations: Consumer Responses to Technology-Mediated Haptic Feedback

Abstract: Individuals often experience incidental device-delivered haptic feedback (e.g., vibrational alerts accompanying messages on mobile phones and wearables), yet almost no research has examined the psychological and behavioral implications of technology-mediated touch on consumers. Drawing from theories in social psychology and computer science, we explore how device-delivered haptic feedback may have the capability to augment consumer responses to certain consumer-directed communications. Across four studies, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 49 publications
1
60
0
Order By: Relevance
“…Similar to our results, most users found haptic feedback to provide the greatest degree of presence and to improve the object detection rate (task performance). On the usefulness of haptic feedback, which is implicit in the results of this UX study, it was found in [ 32 ] that device-driven haptic feedback may lead to increase consumer responses to certain consumer-directed communications, by improving consumer performance on related tasks and an increased sense of social presence. A more generic study on influence of haptic feedback on emotional arousal, sense of presence, and embodiment in virtual reality, can be found in [ 33 ], where the main conclusions also corroborate those obtained in this work, i.e., more engaging experience is obtained when haptic feedback is used.…”
Section: Experimental Resultsmentioning
confidence: 99%
“…Similar to our results, most users found haptic feedback to provide the greatest degree of presence and to improve the object detection rate (task performance). On the usefulness of haptic feedback, which is implicit in the results of this UX study, it was found in [ 32 ] that device-driven haptic feedback may lead to increase consumer responses to certain consumer-directed communications, by improving consumer performance on related tasks and an increased sense of social presence. A more generic study on influence of haptic feedback on emotional arousal, sense of presence, and embodiment in virtual reality, can be found in [ 33 ], where the main conclusions also corroborate those obtained in this work, i.e., more engaging experience is obtained when haptic feedback is used.…”
Section: Experimental Resultsmentioning
confidence: 99%
“…For instance, Lee and Spence (2008a) investigated the optimal timing of visual and vibrotactile feedback to create perceptions of synchrony between the two modalities. Building on this work, consumer studies have begun to explore consumers’ interaction with mobile devices (e.g., Brasel and Gips, 2014 , Hadi and Valenzuela, 2019 , Petit et al, 2019 ). For instance, Hadi and Valenzuela (2019) found that vibration feedback makes consumers more responsive to mobile messages that appear on a touchscreen.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…The rich literature exploring the role of multisensory design in consumer technologies offers several insights. Studies in this area suggest that combinations of haptic and visual feedback delivered via mobile devices can effectively influence consumers’ responses to stimuli and events (e.g., Hadi and Valenzuela, 2019 , Lee et al, 2009 , Lee and Spence, 2008a , Lee and Spence, 2008b ). For instance, Hadi and Valenzuela (2019) found that pairing mobile message prompts with haptic vibration alerts improved consumers’ responsiveness to the messages due to increased feelings of social presence.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations